Mortality in gold and coal miners in Western Australia with special reference to lung cancer. Issue 3 (August 1979) - Armstrong, B K; McNulty, J C; Levitt, L J; Williams, K A; Hobbs, M S
Abstract : Cohorts of 1974 gold miners and 213 coal miners in Western Australia surveyed for respiratory symptoms, smoking habits, occupational history and radiographic evidence of pneumoconiosis have been followed up for 13-14 years. Overall, neither group had a significantly higher mortality than expected from the experience of Western Australian men in general. Lung cancer mortality was relatively high in the gold miners (59 deaths observed, 40.8 expected) but weakly and inconclusively related to the extent of their underground mining experience. Cigarette smoking may explain the excess of lung cancer in the gold miners because the prevalence of the habit in the latter (66.3%) was higher than in the coal miners (58.7%) or in other men in Western Australia (53.2%). Radiographic evidence of silicosis was present in 21.7% of the gold miners but did not appear to have contributed substantially to their mortality. The coal miners showed a lower than expected rate of lung cancer but an excess of deaths from all other forms of cancer (11 observed, 5.6 expected). This excess was not attributable to any one cancer site and cannot be explained readily.